EDUCAÇÃO PARA EMOÇÃO E AFETO NA ESCOLA: UM OLHAR PARA A FORMAÇÃO DE PROFESSORAS (ES) DE ARTES VISUAIS - LIMA, Hellen Rose de Sousa (2022)
The research presents Emotional Education at school, from the reports of pedagogical practices of teachers of Visual Arts. The general objective is to investigate about education for emotion and affection at school in the context of training visual arts teachers (es) with a view to creating a notebook of pedagogical guidelines. As a reference for this investigative study, the psychoevolutionist, cognitive and social theoretical perspectives were considered, when approaching the discussions around the emotional difficulties of teachers, structure and transformation in the face of the pandemic scenario to which education goes through profound changes at the time of the Remote Teaching Emergency and isolation. It was based on studies by Barbosa (1989), Chamlian (2008), Damásio (1998), Dewey (2010), Ekman (2011), Goleman (1995), Gardner (2007), LeDoux (2007), Nóvoa (1992, 1995, 2002), Read (2016), Santos (2010, 2020), Sartre (2012), Vigotsky (1997, 1998), Wallon (1971, 1995), among other theoretical ones. The methodological course was characterized as qualitative, applied and descriptive research, which elected as participating subjects teachers of Visual Arts from public schools in São Luís. The data collection instruments were: semi-structured interviews, questionnaires and creative workshops. After analyzing the data, it was found that the results were significant, it was evidenced that the emotional health of the teaching professionals has been left aside, and the existence of this gap was observed, proposals for flow and balance were thought through contact with the Art. These proposals were materialized in the product of this research, the Notebook of Pedagogical Orientations. The analyzes and reflections brought in this work help to understand socio-emotional skills as competences that involve all these constructs and that are fundamental for teacher training, as it is necessary to feel emotional to educate and, consequently, to reach the feelings of the learners. It was inferred that although remote teaching was necessary for the non stagnation of academic activities during the pandemic period, it was surrounded by challenges, marked by the difficulty of access, expanding the existing social inequalities, being considered a driver of disorders to the emotional health of children. according to participants' reports, expressing the emotional difficulties in teaching in the face of the pandemic context. The product generated from the research was a booklet of pedagogical guidelines: “A look at emotion in the training of visual arts teachers”. with knowledge and contributions to visual arts teachers.